Analisis Penokohan Tokoh Ainun dalam Novel Habibi dan Ainun Karya Baharudin Jusuf Habibi - HERNI FITRIANI (STKIP Nurul Huda, 2019)
Literature generally involves all aspects of human life and life, events in works of fiction as well as events in everyday life, always carried by a certain character or perpetrators. The formulation of the problem in this analysis is how the characterization of Ainun figure is expository and dramatic in novel Habibie and Ainun Karya Bacharuddin Jusuf Habibie ?. The results of data analysis and discussion, In revealing the figure Ainun figure, the author uses the technique of depiction of figures proposed by Nurgiyantoro, the technique of depiction of characters in a literary work can be distinguished in two techniques, namely expository techniques and dramatic techniques, through the technique of Ainun figure expression in novel Habibie and Ainun by Bacharuddin Jusuf Habibie can be concluded that he is a figure of a very patient, while through dramatic techniques that include skillful techniques, behavioral techniques, techniques of mind and feeling, stream of consciousness techniques, reaction techniques, techniques of reactions of other figures, background and techniques of physical representation, figure Ainun is obedient and obedient to her husband, kind, responsible, has a very patient personality, he is a figure of a figure who likes peace, peace. But he had tested his loyalty to the husband that when he had to live mediocre when he was in Germany, he learned to use the maximum time so that everything can be resolved properly set the menu cheap but healthy, take care of children, husband and work. All he lived with full sincerity. Ainun always provide peace in his family with his personality. After a long time he thought to go back to work as a doctor so he could help his family's economy, but it takes recognition of UI diplomas in Germany and requires an indeterminate time process. After Ainun got back to work, Ainun was confronted with her personal problems when the children were sick and needed her to choose between work and children, based on faith, Ainun sacrificed her job as a doctor to Always be with her son and husband.